Analysis of the Message in the Film “Cinta Tak Seindah Drama Korea” - Yulfa Nur Hidayah; Ken Amasita Saadjad; Sofia Melita; Nurafni Renidamayanti; Agus Wahyudi Putra (Jogjakarta Communication Conference (JCC), 2026)
This study aims to analyze messages in the film “Cinta Tak Seindah Drama Korea” as a representation of the fusion of storytelling styles in contemporary cinema. The research method employed a qualitative descriptive approach using Charles Sanders Peirce’s semiotic theory. The findings reveal that narrative and visual elements are structured to convey messages to the audience. Furthermore, the film uniquely blends storytelling elements characteristic of Korean dramas such as visual aesthetics and dramatic structure while retaining the distinctive traits and narrative approach of Indonesian cinema. Overall, the film “Cinta Tak Seindah Drama Korea” demonstrates the ability of local cinema to both respond to and creatively adapt popular trends. These findings affirm that adapting foreign trends does not immediately erase the identity of local works; rather, it enriches perspectives and strengthens the current position of Indonesian cinema.